The Changes of Poetic Forms in the Contemporary Era - Jahromi, Mohammad Mehdi Torabikhah; Sardehi, Ali Eshghi; Amirahmadi, Abolghasem (Journal of History Culture and Art Research, 2017)
Abstract This study examines the form of poems after Mashrouteh (constitutional revolution of Iran) and explains the literary-semantic function after having a brief look at the poetry in 40s and 50s. This essay aims to answer whether poesy gone through a lot of innovations and changes during years or the change and transition in its form and semantic has taken place gradually. The study looks possible answers whether there has been many innovations and transitions or a gradual change rarely in spite of the general tendency that poets seek innovation in different ways during the history of Persian poetry.